Lower IgA Levels in Chronic Spontaneous Urticaria Are Associated With Lower IgE Levels and Autoimmunity - Sauer, Merle; Scheffel, Jörg; Frischbutter, Stefan; Kolkhir, Pavel; Xiang, Yi-Kui; Siebenhaar, Frank; Altrichter, Sabine; Maurer, Marcus; Metz, Martin; Krause, Karoline (Frontiers in Immunology, 2021)
Background The pathogenesis of chronic spontaneous urticaria (CSU) is still insufficiently understood. Recent findings suggest that immunoglobulins, in particular IgE but also IgA, play a role in the development of CSU. Objective Our aim was to assess differences in clinical and laboratory markers between CSU patients with and without lower levels of serum IgA and IgE. Methods We analyzed the data of 606 patients with CSU by dividing them into four groups based on their IgA and IgE levels. The groups were compared for their spectrum of symptoms, disease activity, concomitant autoimmunity and routine laboratory markers. Autoreactivity was assessed by basophil activation test (BAT). Moreover, IgE-anti-thyroid peroxidase (TPO) was measured. Results Of the patients with lower IgE levels, 66.5% also had lower IgA levels (r=0.316, p<0.001). Patients with lower IgA and lower IgE levels showed a higher prevalence of recurrent angioedema (p=0.03, p=0.04) and concomitant autoimmunity (p=0.006, p<0.001). Autoreactivity was also found more frequently in patients with lower IgA and lower IgE levels (p=0.003, p<0.001). Reduced basophil counts were linked to both, lower IgA and lower IgE levels (p<0.001), whereas low eosinophil counts were primarily present in patients with lower IgE levels (p=0.04, p<0.001). Patients with elevated IgE-anti-TPO levels had lower IgA (p=0.007) and IgE levels (p=0.001). Conclusion Lower IgA levels in CSU are linked to lower IgE levels and features of autoimmune urticaria. Our findings encourage to screen CSU patients for serum IgA and IgE levels and to further assess their role as disease biomarkers.